Impact of γ-irradiation on dielectric and electric properties of TlInS₂ crystals - Sardarly, R.M.; Samedov, O.A.; Salmanov, F.T.; Aliyeva, N.A. (Вопросы атомной науки и техники, 2019)
The effect of γ-irradiation on the relaxor properties of the TlInS₂ compound have been studied. It is established that in this compound the Vogel-Fulcher temperature (Tf) shifts towards the low temperatures, and the Burns temperature (Td) moves towards the high temperatures. As a result, the temperature range for the existence of a relaxor state extends by ∼ 40 K. The presence of hopping conduction is established and the parameters characterizing this mechanism are determined. Вивчено вплив γ-опромінення на релаксорні властивості з'єднання TlInS₂. Встановлено, що в цьому з'єднанні температура Фогеля-Фулчера (Tf) зміщується в бік низьких температур, а температура Бернса (Td) – у сторону високих температур. В результаті температурний інтервал існування релаксорного стану розширюється на ∼ 40 K. Встановлено наявність стрибкової провідності і визначенo параметри, що характеризують даний механізм. Изучено влияние γ-облучения на релаксорные свойства соединения TlInS₂. Установлено, что в этом соединении температура Фогеля-Фулчера (Tf) смещается в сторону низких температур, а температура Бернса (Td) – в сторону высоких температур. В результате температурный интервал существования релаксорного состояния расширяется на ∼ 40 K. Установлено наличие прыжковой проводимости и определены параметры, характеризующие данный механизм.